Identifying defects on solar cells using magnetic field measurements and artificial intelligence trained by a finite-element-model - Buehler Kjell; Kaufmann Kai; Patzold Markus; Sprenger Mawe; Schoenfelder Stephan (EPJ Photovoltaics, 2023)
Renewable energies have an increasing share in the energy supply. In order to ensure the security of this supply, the reliability of the systems is therefore increasingly important. In photovoltaic modules or in manufacturing, defective solar cells due to broken busbars, cross-connectors or faulty solder joints must be detected and repaired quickly and reliably. This paper shows how the magnetic field imaging method can be used to detect defects in solar cells and modules without contact during operation. For the evaluation of the measurement data several neural networks were used, which were trained with the help of results from finite element simulations. Different training data sets were set up in the simulation model by varying the electrical conductivities of the different parts of the solar cell. The influence of the neural network type and the variation of the training data sets as well as an advantage of a combination of simulated and experimental training data are presented and discussed.